Identifying creative research accomplishments: methodology and results for nanotechnology and human genetics - Thomas Heinze; Philip Shapira; Jacqueline Senker; Stefan Kuhlmann (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2006)
Motivated by concerns about the organizational and institutional conditions that foster research creativity in science, we focus on how creative research can be defined, operationalized, and empirically identified. A functional typology of research creativity is proposed encompassing theoretical, methodological and empirical developments in science. We then apply this typology through a process of creative research event identification in the fields of nanotechnology and human genetics in Europe and the United States, combining nominations made by several hundred experts with data on prize winners. Characteristics of creative research in the two respective fields are analyzed, and there is a discussion of broader insights offered by our approach.
urn:nbn:de:0011-n-454589
Keywords: 330; Forschung; Kreativität; Nanotechnologie; Biotechnische Forschung; USA; Europa